(3JbQjQGJ GdTjN eMeO MSjf GdCUagGfj GdCUhdjI Ydi eJf GdcaGjIs - (3GdCUagGfj, abjg GdadGSaI, eMeO MSjf Hf eMeO MSf, J (B1361 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3adcd Yde eSGFd hbVGjG eJTbbI jLeYgG ZQV hGMO Ohf GdYde dCLdg hGdeSGFd ehVhYGJ (B... (3JUOjbjI hGdeHGOF GdJUOjQjI aj GdCUhd JfbSe Edi eHGOF dZhjI (B...s
(3BNQgG (B:s
... (3HGdcSQ hdcf GdJMbjb ef gPG GdJaUjd jHjf GdUhQ HCf jbGd HhLhH GdGLJfGH Yf GdedGbj HGdaJM abW aj LejY GdUhQ EdG aj eG cGf GdedGbj (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/106s
(3bO jchf (B( (3fgGjI GdOQGjI aj TQM GdcaGjI (B) (3dgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs